Ethics and neuromarketing : implications for market research and business practice - Thomas, Andrew R.; Pop, Nicolae Al; Iorga, Ana Maria; Ducu, Cristian (Springer International Publishing, 2017)
This book addresses the emerging field of neuromarketing, which, at its core, aims to better understand the impact of marketing stimuli by observing and interpreting human emotions. It includes contributions from leading researchers and practitioners, venturing beyond the tactics and strategies of neuromarketing to consider the ethical implications of applying powerful tools for data collection. The rationale behind neuromarketing is that human decision-making is not primarily a conscious process. Instead, there is increasing evidence that the willingness to buy products and services is an emotional process where the brain uses short cuts to accelerate the decision-making process. At the intersection of economics, neuroscience, consumer behavior, and cognitive psychology, neuromarketing focuses on which emotions are relevant in human decision-making, and uses this knowledge to make marketing more effective. The knowledge is applied in product design; enhancing promotions and advertising, pricing, professional services, and store design; and improving the consumer experience as a whole. The foundation for all of this activity is data gathering and analysis. Like many new processes and innovations, much of neuromarketing is operating far ahead of current governmental compliance and regulation and thus current practices are raising ethical issues. For example, facial recognition software, used to monitor and detect a wide range of micro-expressions, has been tested at several airports--under the guise of security and counterterrorism. To what extent is it acceptable to screen the entire population using these powerful and intrusive techniques without getting passengers' consent? Citing numerous examples from the public and private sectors, the editors and contributing authors argue that while the United States has catalyzed technological advancements, European companies and governments are more progressive when it comes to defining ethical parameters and developing policies. This book details many of those efforts, and offers rational, constructive approaches to laying an ethical foundation for neuromarketing efforts.